Ba2Ln1−xMn2Te5 (Ln = Pr, Gd, and Yb; x = Ln vacancy): syntheses, crystal structures, optical, resistivity, and electronic structure. Issue 19 (28th April 2021) - Panigrahi, Gopabandhu; Jana, Subhendu; Ishtiyak, Mohd; Narayanswamy, S.; Bhattacharjee, Pinaki P.; Ramanujachary, K. V.; Niranjan, Manish K.; Prakash, Jai
Abstract : Three new cation deficient quaternary tellurides, Ba2 Ln1− x Mn2 Te5 ( x = Ln vacancy), were discovered by the exploratory solid-state method. Abstract : Three new isostructural quaternary tellurides, Ba2 Ln1− x Mn2 Te5 (Ln = Pr, Gd, and Yb), have been synthesized by the molten-flux method at 1273 K. The single-crystal X-ray diffraction studies at 298(2) K showed that Ba2 Ln1− x Mn2 Te5 crystallize in the space group – C 2/ m of the monoclinic crystal system. There are six unique crystallographic sites in this structure's asymmetric unit: one Ba site, one Ln site, one Mn site, and three Te sites. The Ln site in the Ba2 Ln1− x Mn2 Te5 structure is partially filled, which leaves about one-third of the Ln sites vacant (□) for Pr and Gd compounds. These structures do not contain any homoatomic or metallic bonding and can be charge-balanced as (Ba 2+ )2 (Gd/Pr 3+ )2/3 (Mn 2+ )2 (Te 2− )5 . The refined composition for the Yb compound is Ba2 Yb0.74(1) Mn2 Te5 and can be charge-balanced with a mixed valence state of Yb 2+ /Yb 3+ . The crystal structures of Ba2 Ln1− x Mn2 Te5 consist of complex layers of 2∞[Ln1− x Mn2 Te5 ] 4− stacked along the [100] direction, with Ba 2+ cations separating these layers. The Ln atoms are bound to six Te atoms that form a distorted octahedral geometry around the central Ln atom. Each Mn atom in this structure is coordinated to four Te atoms in a distorted tetrahedral fashion. These LnTe6 and MnTe4 units are the main building blocks of the Ba2 Ln1− x Mn2 Te5 structure. The optical absorption study performed on a polycrystalline Ba2 Gd2/3 Mn2 Te5 sample reveals a direct bandgap of 1.06(2) eV consistent with the DFT study. A semiconducting behavior was also observed for polycrystalline Ba2 Gd2/3 Mn2 Te5 from the resistivity study. The temperature-dependent magnetic studies on a polycrystalline sample of Ba2 Gd2/3 Mn2 Te5 did not reveal any long-range magnetic order down to 5 K. The effective magnetic moment ( μ eff ) of 10.37 μ B calculated using the Curie–Weiss law is in good agreement with the theoretical value ( μ cal ) of 10.58 μ B .